2016
DOI: 10.1186/s13018-016-0429-3
|View full text |Cite
|
Sign up to set email alerts
|

The reliability and validity of the Turkish version of the Oxford Elbow Score

Abstract: Background: Objective measures of outcome ensure reliable decisions with regard to treatment planning. Oxford Elbow Score (OES) is one of the common outcome measures used for assessing quality of life of patients with elbow disorders. OES consists of three domains: pain, elbow function and social/psychological. The aim of this study is to test the validity and reliability of the Turkish version of the OES. Methods: The study's sample includes 82 patients with elbow problems. The original version of the OES was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 10 publications
2
14
0
Order By: Relevance
“…We hypothesized strong correlation between the OES and the QuickDASH score as well as similar domains from the physical component section of the SF-36. Results confirmed this hypothesis showing a strong correlation health and vitality subscales [18]. The original OES study showed divergent validity with low correlations between all three Oxford elbow score domains and the SF-36 mental health and general health perception domains [9].…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…We hypothesized strong correlation between the OES and the QuickDASH score as well as similar domains from the physical component section of the SF-36. Results confirmed this hypothesis showing a strong correlation health and vitality subscales [18]. The original OES study showed divergent validity with low correlations between all three Oxford elbow score domains and the SF-36 mental health and general health perception domains [9].…”
Section: Discussionsupporting
confidence: 61%
“…Results from the general health subscale of the PCS and all MCS subscales were non-significant. Studies by Yosmaoglu et al showed non-significant results for correlation between the general health and vitality subscales [ 18 ]. The original OES study showed divergent validity with low correlations between all three Oxford elbow score domains and the SF-36 mental health and general health perception domains [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cross-cultural adaptation and validation of the OES have already been done in five languages: Dutch, 7 Danish, 22 Persian, 9 Turkish, 28 and German. 20 An adaptation to the Italian language and culture has not yet been done.…”
mentioning
confidence: 99%